Four weddings and a kiss [large type] : a western bride collection - Connealy, Mary; Hatcher, Robin Lee; Clopton, Debra; Brownley, Margaret (Thorndike Press, a part of Gale, Cengage Learning, 2014)
In 1885, five western preachers sit around a campfire talking about unlikely couples they've seen God bring together, as told in stories by Mary Connealy, Robin Lee Hatcher, Debra Clopton and Margaret Brownley. Original.